Боротьба зі злочинністю в аспекті її організації - Бандурка, О. М.; Bandurka, O. M.; Литвинов, О. М.; Lytvynov, O. M.; ORCID: http://orcid.org/0000-0002-0240-5517; ORCID: http://orcid.org/0000-0003-2952-8258 (Вісник Кримінологічної асоціації України. - 2015. - № 3 (11). - С. 9-18., 2015)
Статтю присвячено аналізу організаційних засад боротьби зі злочинністю. Розглянуто цілі, завдання та функції управління боротьбою зі злочинністю, зокрема, планування, координація, контроль та вимірювання ефективності.

Combating crime includes two main aspects: criminal and legal, that contains detection, solving, investigating crimes and prosecuting perpetrators to the liability set by the law; and criminological that covers the study of crime, its causes and taking measures for their elimination or neutralization. Combating crime is a kind of social activity and requires organization. Proper organization of combating crime is the essential condition to its effectiveness. Organization of combating crime includes: crime analysis, determining the goals and priori-ties, planning of measures directed on ighting against crime, coordination and assessment of ef iciency. Crime analysis is a unity of cognition and assessment. It can be carried out across the country, within regions, districts, neighborhoods. Correctly formulated objectives define the main directions of the fight against crime, act as a factor that mobilizes, serve as criteria for assessment of the ef-fectiveness of law enforcement agencies’ activities in combating crime. A special role in organizing the fight against crime belongs to planning of measures di-rected on the suppression of crimes, weakening and neutralization of the fac-tors that cause them. The object of control as a management function is activity of the subjects of combating crime on the implementation of measures provided by the plans and programs of combating crime as well as measures, periodic or systematic implementation of which is entrusted to the relevant subjects by the current law. Coordination assists to create a single front to combat crime, which is a prerequisite for success. Practical possibility to measure the effectiveness of efforts in combating crime directly depends on the fact how properly objec- tives and tasks are scientifically grounded in this area, as well as the presence of the system of indicators, on which basis any activity in combating crime can be evaluated. However, for the assessment of the state of combating crime in general and in its some areas we should have own set of indicators.

Статья посвящена анализу организационных основ борьбы с преступностью. Рассмотрены цели, задачи и функции управления борьбой с преступностью, в том числе планирование, координация, контроль и измерение эффективности.
Бандурка, О. М. Боротьба зі злочинністю в аспекті її організації / О. М. Бандурка, О. М. Литвинов // Вісник Кримінологічної асоціації України. - 2015. - № 3 (11). - С. 9-18.
Бандурка, О. М., Литвинов О. М. "Боротьба зі злочинністю в аспекті її організації." Вісник Кримінологічної асоціації України 3 (2015): 9-19.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; боротьба зі злочинністю; організація; управління; планування; координація; контроль; ефективність; combating crime; organization; management; planning; coordination; control; efficiency; борьба с преступностью; организация; управление; планирование; координация; эффективность; combating crime